Corporate Social Responsibility and Financial Performance. Theoretical and Empirical Aspects - Lech, Aleksandra (Comparative Economic Research. Central and Eastern Europe, 2013)
The aim of this paper is to examine the impact of Corporate Social Responsibility (CSR) rules on the financial performance of companies. In a theoretical part the author analyses selected economic theories that might justify a positive relationship between CSR and profitability, as well as explains the mechanism by which CSR might positively enhance economic performance from the stakeholders’ perspective. In an empirical part the author discusses selected econometric studies on the link between CSR and economic performance of companies, both from developed and developing countries. The article also contains the results of the author’s own research on the relationship between CSR and economic performance of the largest Polish companies on the Warsaw Stock Exchange. The scope of the author’s own research is the period 1Q 2010 –IIIQ 2012. The research shows that participation in the Respect Inde X(indicator of CSR in the author’s model) is not statistically significant in determining the financial performance of Polish firms.